Critical citizenship through the curriculum: comparative analysis of teacher experiences from Chile and Costa Rica in citizenship formation - Calderón Azofeifa, Mauricio (2024)
This essay is an analysis of the vision of the citizenship and its approach in the official curriculum through the experiences of teachers in the classroom, using a comparative method between Costa Rica and Chile, discovering similarities and differences in the Civic Education curriculum that is taught to young students during their last year in secondary school (17 to 18 years approximately). What kind of learnings are promoted? What challenges and possibilities exist today during the work of critical citizenships in the classroom? We discovered that the ten year difference between the curriculums make differences in conceptual and processual contents, however, there are similarities in the attitudinal and the concern of the States in order to build a democratic society through active and critical citizenships in the classroom, which gives the teacher a central and essential role, because it is the teacher who has to make a reality the ideals of civic education to the school in different contexts.